Prognostic Indicator for Clinical Babesiosis in Cattle - Kumar, Bipin; Mondal, D.B.; Jithin , M.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Present Study has been carried out on the animals suffering from clinical bovine babesiosis in the Patna districts of Bihar, India. A total number of 36 lactating cows of different breeds and ages were included in the study to develop a prognostic indicator card for better and economic management of disease. There are two types of prognostic indicator systems that has been evolved viz numerical and categorical on the basis of oxidant marker, antioxidant status, trace mineral status, hematological changes and vital parameter changes between dead and survived suffering animals. Erythrocytic LPO in succumbed cases were significantly (P
Keywords: Oxidative marker; Babesia bigemina; prognosis; Ixodidae; icterus